2017
DOI: 10.1051/0004-6361/201730932
|View full text |Cite
|
Sign up to set email alerts
|

Search and modelling of remnant radio galaxies in the LOFAR Lockman Hole field

Abstract: Context. The phase of radio galaxy evolution after the jets have switched off, often referred to as the remnant phase, is poorly understood and very few sources in this phase are known. Aims. In this work we present an extensive search for remnant radio galaxies in the Lockman Hole, a well-studied extragalactic field. We create mock catalogues of low-power radio galaxies based on Monte Carlo simulations to derive first-order predictions of the fraction of remnants in radio flux limited samples for comparison w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
189
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(210 citation statements)
references
References 61 publications
20
189
1
Order By: Relevance
“…Brienza et al: Radio spectral properties and jet duty cycle in the restarted radio galaxy 3C388 This is becoming increasingly evident through recent observational campaigns of remnant radio galaxies detecting small fractions, up to 10%, of these sources (see e.g. Brienza et al 2017;Godfrey et al 2017;Mahatma et al 2018), and also through radio galaxy modelling and simulations, which predict visibility timescales for the remnant plasma of the order of a few tens of Myr (e.g. Brienza et al 2017;Godfrey et al 2017;Hardcastle 2018;English et al 2019).…”
Section: Duty Cyclementioning
confidence: 99%
“…Brienza et al: Radio spectral properties and jet duty cycle in the restarted radio galaxy 3C388 This is becoming increasingly evident through recent observational campaigns of remnant radio galaxies detecting small fractions, up to 10%, of these sources (see e.g. Brienza et al 2017;Godfrey et al 2017;Mahatma et al 2018), and also through radio galaxy modelling and simulations, which predict visibility timescales for the remnant plasma of the order of a few tens of Myr (e.g. Brienza et al 2017;Godfrey et al 2017;Hardcastle 2018;English et al 2019).…”
Section: Duty Cyclementioning
confidence: 99%
“…at least for Fanaroff-Riley type II (FR-II; Fanaroff & Riley 1974) sources, constrain the lobe magnetic field strengths to be substantially lower than those implied by equipartition (Croston et al 2005;Ineson et al 2017). Furthermore, low-sensitivity, narrow-bandwidth observations from the previous generation of radio telescopes may not accurately trace the oldest radiating particles since last injection -a feature of the rapidly fading nature of synchrotron radiation that also prevents detections of switchedoff radio galaxies even in sensitive low frequency surveys (Brienza et al 2016(Brienza et al , 2017Mahatma et al 2018).…”
Section: Spectral Agesmentioning
confidence: 99%
“…In order to test this with a large sample, sensitivity is crucial. Studies of remnants with the LOw Frequency ARray (LOFAR; van Haarlem et al 2013) in the Herschel-ATLAS field (Mahatma et al 2018), for sources > 80 mJy at 150 MHz, and in the similar LOFAR study by Brienza et al (2017), found upper-limit remnant fractions of ∼ 10 per cent; these are potentially a larger percentage of remnants than the percentage found in 3CRR, although this is clearly a non-systematic comparison.…”
Section: Introductionmentioning
confidence: 99%